2008
DOI: 10.1371/journal.pone.0003046
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Reversible Recruitment of Early Visual Cortex for Touch

Abstract: BackgroundThe loss of vision has been associated with enhanced performance in non-visual tasks such as tactile discrimination and sound localization. Current evidence suggests that these functional gains are linked to the recruitment of the occipital visual cortex for non-visual processing, but the neurophysiological mechanisms underlying these crossmodal changes remain uncertain. One possible explanation is that visual deprivation is associated with an unmasking of non-visual input into visual cortex.Methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
200
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(234 citation statements)
references
References 61 publications
26
200
4
Order By: Relevance
“…Primary visual areas in the occipital lobes were subject to less routine stimulation. Previous studies show rapid and profound occipital neuroplastic changes under visual deprivation (Merabet et al 2008). We believe that the same mechanism may underlie our findings.…”
Section: Discussionsupporting
confidence: 86%
“…Primary visual areas in the occipital lobes were subject to less routine stimulation. Previous studies show rapid and profound occipital neuroplastic changes under visual deprivation (Merabet et al 2008). We believe that the same mechanism may underlie our findings.…”
Section: Discussionsupporting
confidence: 86%
“…Consistent with this suggestion, studies have demonstrated that the visual cortex of blind individuals is activated during tasks such as Braille reading (Cohen et al, 1997;Sadato et al, 1996) and haptic object recognition (Amedi, Raz, Azulay, Malach, & Zohary, 2010). Moreover, the existence of networks between vision and touch in normally sighted individuals is supported by neuroimaging studies; visual areas have been shown to be activated during tactile orientation discrimination (Sathian & Zangaladze, 2002;Sathian, Zangaladze, Epstein, & Grafton, 1999), haptic object recognition (Amedi, Jacobson, Hendler, Malach, & Zohary, 2002;Amedi et al, 2010;Deibert, Kraut, Kremen, & Hart, 1999;James, Humphrey, Gati, Servos, Menon, & Goodale, 2002;Pietrini et al, 2004), and Braille reading in sighted subjects following 5 days of complete visual deprivation (Merabet et al, 2008). Furthermore, there is behavioral evidence for the influence of tactile inputs on visual perception.…”
Section: Introductionmentioning
confidence: 68%
“…Thus, a plausible prediction of the tactile experience hypothesis is that the most pronounced acuity enhancement will occur on skin areas receiving the greatest daily stimulation. In contrast, prolonged blindfolding of sighted participants reportedly enhances finger tactile acuity (Kauffman et al, 2002;Facchini and Aglioti, 2003;Merabet et al, 2008) and acuity of other skin areas (Zubek et al, 1964), even without training. Thus, a plausible prediction of the visual deprivation hypothesis is that blind participants will show enhanced acuity throughout the body surface.…”
Section: Introductionmentioning
confidence: 82%
“…This happens in blindfolded sighted participants (Merabet et al, 2007(Merabet et al, , 2008 and blind participants (Sadato et al, 1996(Sadato et al, , 1998(Sadato et al, , 2002(Sadato et al, , 2004Cohen et al, 1999;Burton et al, 2002Burton et al, , 2006Ptito et al, 2005;Stilla et al, 2008). Several lines of evidence suggest a functional role for cross-modal plasticity: a congenitally blind Braille reader developed alexia for Braille after suffering a bilateral occipital stroke , occipital transcranial magnetic stimulation (TMS) impairs blind participants' tactile performance (Cohen et al, 1997(Cohen et al, , 1999Kupers et al, 2007), and occipital TMS elicits sensations on the fingers in some participants (Ptito et al, 2008).…”
Section: Possible Neural Mechanismsmentioning
confidence: 99%